Conductive sheet and manufacturing method thereof

JP7645118B2Active Publication Date: 2025-03-13ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021057789
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-03-13
Estimated Expiration
2041-03-30

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、微細パターンを形成する場合であっても密着性に優れる導電性シート、及びその製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645118000003
    Figure 0007645118000003
  • Figure 0007645118000004
    Figure 0007645118000004
  • Figure 0007645118000005
    Figure 0007645118000005
Patent Text Reader

Abstract

To provide a conductive sheet having high adhesion even in the case of forming a fine pattern, and a method for producing the same.SOLUTION: A conductive sheet has a substrate, a particle layer that is laminated on the substrate and is combined with particles containing a transition metal, and a joint. The joint joins the tips of the particles of the particle layer projecting to the substrate, to the substrate.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive sheet and a method for producing the same. [Background technology]

[0002] Structures containing transition metal particles arranged on a substrate are used for various purposes. For example, a layer of transition metal particles arranged on a substrate can be used as a conductive material. In addition, by forming the layer of transition metal particles into a fine thin line pattern, it can be used as a transparent conductive material, for example, as a part of a transparent electrode used in a touch panel or display.

[0003] Such a layer of transition metal particles can be produced by applying and / or printing an ink containing transition metal particles onto a substrate. In this case, it is known to provide an intermediate layer on the substrate to improve adhesion between the substrate and the layer of transition metal particles. For example, Patent Document 1 discloses providing an insulating resin layer over a relatively wide area of ​​the substrate, and Patent Document 2 discloses providing an intermediate layer by a droplet ejection method. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2006-62135 A [Patent Document 2] JP 2003-315813 A Summary of the Invention [Problem to be solved by the invention]

[0005] Incidentally, when a finer thin line pattern or the like is formed from a layer of transition metal particles arranged on a substrate in order to obtain a transparent conductive material, the above-mentioned intermediate layer is preferably provided only between the thin line pattern and the substrate, from the viewpoint of not compromising costs and transparency, and is preferably not formed in areas on the substrate where the thin line pattern is not present.

[0006] However, it is generally not easy to make the intermediate layer and the layer of transition metal particles overlap, and as the fine line pattern is made thinner to improve transparency, it becomes more difficult to provide the intermediate layer only between the fine line pattern and the substrate, because the fine line pattern and the intermediate layer pattern must be arranged while aligning the pattern positions. Therefore, in order to achieve a conductive sheet that requires higher transparency, it is desirable to develop a method that is completely different from the method of depositing an intermediate layer and forming a layer of transition metal particles on it, as in Patent Documents 1 and 2.

[0007] The present invention has been made in consideration of the above problems, and aims to provide a conductive sheet that has excellent adhesion even when a fine pattern is formed, and a manufacturing method thereof. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above problems, and have found that a minute bonded body that bonds the transition metal particles to the substrate is formed between the substrate and the particle layer by passing through a specific process, thereby solving the above problems, and have completed the present invention.

[0009] That is, the present invention is as follows. [1] A substrate; a particle layer having transition metal-containing particles bonded thereto, the particle layer being laminated on the substrate; a joint; The joint portion connects a tip of a particle in the particle layer protruding toward the substrate to the substrate. Conductive sheet. [2] The joint is confirmed as a part having a lower contrast than the particle layer and the substrate in a transmission electron image of a cross section of the conductive sheet obtained by a transmission electron microscope. The conductive sheet according to [1]. [3] The contact cross-sectional length L0 between the substrate and the joint is 1.0 nm or more and 500 nm or less. The conductive sheet according to [1] or [2]. [4] The contact angle θ between the joint and the base material is 90° or less. The conductive sheet according to any one of [1] to [3]. [5] The cross-sectional length L at the mid-height of the joint 1 / 2 is smaller than the contact cross-sectional length L0 between the base material and the joint; The conductive sheet according to any one of [1] to [4]. [6] The cross-sectional length L at the mid-height of the joint 1 / 2 The ratio of the contact cross-sectional length L0 to the joint (L 1 / 2 / L0) is 0.1 or more and 1.0 or less, The conductive sheet according to any one of [1] to [5]. [7] The curvature of the portion of the protruding particle that contacts the joint is 1.0 μm -1 More than 1000μm -1 Below is the The conductive sheet according to any one of [1] to [6]. [8] The coverage of the substrate at the joint is 1.0% or more and 50% or less. The conductive sheet according to any one of [1] to [7]. [9] A gap between the protruding particle and the substrate, which is joined by the joint, is 1 nm or more and 100 nm or less. The conductive sheet according to any one of [1] to [8].

[10] The substrate has a plurality of layers. The conductive sheet according to any one of [1] to [9].

[11] The substrate has a surface layer containing a silicon compound. The conductive sheet according to any one of [1] to

[10] .

[12] The substrate is a plastic. The conductive sheet according to any one of [1] to

[11] .

[13] The plastic is polyethylene terephthalate. The conductive sheet according to

[12] .

[14] The transition metal comprises a metal of Group 11 of the IUPAC Periodic Table; The conductive sheet according to any one of [1] to

[13] .

[15] The transition metal comprises copper. The conductive sheet according to

[14] .

[16] The average particle size of the particles constituting the particle layer is 1.0 nm or more and 500 nm or less. The conductive sheet according to any one of [1] to

[15] .

[17] The particle layer has a thickness of 30 nm or more and 1000 μm or less. The conductive sheet according to any one of [1] to

[16] .

[18] The particle layer forms a continuous pattern having openings. The conductive sheet according to any one of [1] to

[17] .

[19] The pattern is a pattern formed by intersecting a plurality of thin lines. The conductive sheet according to

[18] .

[20] The line width of the thin line is 100 nm or more and 1000 μm or less. The conductive sheet according to

[19] . 〔twenty one〕 The pitch of the thin lines is 1.0 μm or more and 1000 μm or less. The conductive sheet according to

[19] or

[20] . 〔twenty two〕 Visible light transmittance is 70% or more and 99% or less. The conductive sheet according to any one of [1] to

[21] . 〔twenty three〕 Sheet resistance is 0.001 Ω cm -2 More than 20Ωcm -2 Below is the The conductive sheet according to any one of [1] to

[22] . 〔twenty four〕 The conductive sheet according to any one of [1] to

[23] is provided. Touch panel. 〔twenty five〕 The conductive sheet according to any one of [1] to

[23] is provided. display.

[26] The conductive sheet according to any one of [1] to

[23] is provided. Heater.

[27] The conductive sheet according to any one of [1] to

[23] is provided. Electromagnetic wave shielding.

[28] The conductive sheet according to any one of [1] to

[23] is provided. antenna.

[29] a film forming step of forming a precursor thin film on a substrate; an exposure step of exposing the precursor thin film to a gas containing hydrogen atoms at a partial pressure of 50 to 1000 Pa for 50 to 1000 seconds; and a plasma reaction step of reacting the precursor thin film exposed to the gas with plasma for 120 seconds or more and 2000 seconds or less to obtain a conductive sheet. A method for manufacturing a conductive sheet.

[30] The atmosphere of the plasma reaction process contains a gas that is a molecule containing a hydrogen atom. A method for producing the conductive sheet according to

[29] .

[31] The atmosphere of the plasma reaction step includes a rare gas. A method for producing a conductive sheet according to

[29] or

[30] .

[32] In the plasma reaction step, microwave plasma is used. A method for producing a conductive sheet according to any one of

[29] to

[31] . Effect of the Invention

[0010] According to the present invention, it is possible to provide a conductive sheet that has excellent adhesion even when a fine pattern is formed, and a method for producing the same. [Brief description of the drawings]

[0011] [Figure 1] 1 is a schematic cross-sectional view showing an example of a conductive sheet according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged view of a cross section S1 in FIG. [Diagram 3] FIG. 3 is an enlarged view of a cross section S2 in FIG. [Figure 4] FIG. 2 is a schematic top view illustrating an example of a conductive sheet according to the present embodiment. [Diagram 5] 1 shows a transmission electron image and a backscattered electron image of a joint in Example 1 taken by a transmission electron microscope. [Figure 6] 1 shows a transmission electron image and a backscattered electron image of a joint in Example 2 taken by a transmission electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail with reference to the drawings as necessary, but the present invention is not limited to this, and various modifications are possible without departing from the gist of the present invention. In the drawings, the same elements are given the same symbols, and duplicated explanations will be omitted. Furthermore, positional relationships such as up, down, left, and right are based on the positional relationships shown in the drawings, unless otherwise specified. Furthermore, the dimensional ratios of the drawings are not limited to those shown in the drawings.

[0013] 1.Conductive sheet The conductive sheet of the present embodiment includes a substrate, a particle layer formed by bonding particles containing a transition metal and laminated on the substrate, and a joint, and the joint connects the tips of the particles in the particle layer that protrude toward the substrate to the substrate.

[0014] Fig. 1 shows a schematic cross-sectional view illustrating an example of a conductive sheet of the present embodiment, and Fig. 2 shows an enlarged view of a cross section S in Fig. 1. Fig. 1 shows a schematic cross-sectional view of a conductive sheet 100 in which a particle layer 10 is disposed on a substrate 20. The particle layer 10 shown in Fig. 1 is expressed as a particle layer formed by bonding transition metal particles, and the cross section may have voids 11.

[0015] As shown in FIG. 2, the conductive sheet 100 of this embodiment has a joint 30 that joins the substrate 20 and the particle layer 10 at the interface between the substrate 20 and the particle layer 10, thereby further improving the adhesion between the particle layer 10 and the substrate 20. In particular, the joint 30 of this embodiment can be formed so as to join the tip of the particle 12 protruding from the particle layer 10 to the substrate 20 by a manufacturing method described later. Therefore, when attempting to form a finer fine line pattern or the like using the particle layer 10, for example, it is not necessary to coat an intermediate layer for improving adhesion on the entire substrate, or to arrange a layer of transition metal particles so that the intermediate layer coated on a part of the substrate and the layer of transition metal particles overlap. Hereinafter, each configuration of the conductive sheet of this embodiment will be described in detail.

[0016] 1.1.Joints As shown in FIG. 2, the joint 30 connects the tip of the particle 12 protruding from the substrate 20 in the particle layer 10 to the substrate 20. As a specific example, FIG. 5 shows a transmission electron image and a backscattered electron image of the joint in Example 1 described later by a scanning transmission electron microscope (STEM). In this backscattered electron image, the tip of the particle 12 appears to be in contact with the substrate 20, but surprisingly, in the transmission electron image, the tip of the particle 12 is actually a part with lower contrast than the particle layer 10 (particle 12) containing a transition metal and the substrate 20, that is, a part with lower electron density, and is different from the particle 12 and the substrate 20. The mechanism of the bonding between the particle layer 10 and the substrate 20 by the joint 30 is not particularly limited, but it is conceivable that the joint 30 can coincidentally adhere favorably to both the particle layer 10 and the substrate 20 by the structure of the low electron density observed as described above, and as a result, the joint 30 can favorably bond the particle layer 10 and the substrate 20.

[0017] In this embodiment, a joint between the particle 12 and the substrate 20 that can be confirmed in a reflected electron image and that is confirmed in a transmitted electron image as a part with lower contrast than the particle layer and the substrate is defined as the joint 30. That the joint 30 is different from the particle 12 and the substrate 20 can be confirmed by, for example, observing that the joint 30 is a part with lower contrast than the particle layer and the substrate in a transmitted electron image and / or by observing that the joint 30 is destroyed by irradiating an electron beam near the joint 30 for a long period of time.

[0018] 3 shows an example of an enlarged view of cross section S2 in FIG. 2, that is, an enlarged view of joint 30. The shape of joint 30 is not particularly limited, but has, for example, a contact surface 31 with substrate 20, a contact surface 33 with particle 12, and a side surface 32 connecting contact surface 31 and contact surface 33. In FIG. 3, the side surface 32 also has a surface that curves toward the center.

[0019] 1.1.1. Contact Surface 31 and Contact Surface 33 A contact surface 31 between the bonding portion 30 and the substrate 20 is a flat surface that fits along the surface of the substrate 20, and the bonding portion 30 is in close contact with the substrate 20 at this contact surface 31. The length of this contact surface 31 (contact cross-sectional length L0) is preferably 1.0 to 500 nm, more preferably 5.0 to 400 nm, and further preferably 10 to 300 nm. When the contact cross-sectional length L0 is within the above range, the adhesion between the bonding portion 30 and the substrate 20 is further improved, and thus the adhesion between the particle layer 10 and the substrate 20 tends to be further improved.

[0020] Similarly, the contact surface 33 between the joint 30 and the particle 12 is a curved surface that follows the surface of the particle 12, and the joint 30 is in close contact with the particle layer 10 at this contact surface 33. The larger the contact surface 33 is, the more the adhesion between the joint 30 and the particle layer 10 is improved, and therefore the adhesion between the particle layer 10 and the substrate 20 tends to be improved.

[0021] The thickness of the bonded portion 30 tends to depend on the size of the particles 12 and the proximity (gap G) between the particles 12 and the substrate 20, and the larger the particles 12 and the closer the gap G, the thicker the bonded portion 30 tends to be. The thicker the bonded portion 30, the larger the size of the contact surface 31 (contact cross-sectional length L0) and the size of the contact surface 33 tend to be. Therefore, by controlling the size of the particles 12 and the gap G, it is possible to control the contact cross-sectional length L0 and the size of the contact surface 33.

[0022] As shown in each photograph of FIG. 5, the bond 30 is formed between the particle 12 and the substrate 20, and is not formed on the entire surface of the substrate 20. As an index expressing this, the coverage of the substrate 20 by the bond 30 can be used. This coverage is preferably 1.0 to 50%, more preferably 1.0 to 25%, and even more preferably 1.0 to 15%, assuming that the interfacial distance of the region between the particle layer 10 and the substrate 20 is 100%. When the coverage is within the above range, the adhesion between the particle layer 10 and the substrate 20 tends to be further improved.

[0023] Note that "the distance of the interface between the region between the particle layer 10 and the substrate 20 is taken as 100%" means that in calculating the coverage rate, the portion of the substrate 20 on which the particle layer 10 is not formed is excluded, and the coverage rate is calculated on the portion on which the particle layer 10 is formed. More specifically, when the particle layer 10 has a cross section of a thin metal wire as shown in FIG. 1, the coverage rate may be calculated for the cross section.

[0024] 1.1.2. Side 32 The side surface 32 is a portion that connects the contact surface 31 and the contact surface 33. As shown in Fig. 3, the joint 30 may have an inwardly curved side surface 32. There is no particular limitation on the reason why the joint 30 has the inwardly curved side surface 32. It is presumed that, in the process of forming the joint 30, the transition metal-containing particles 12 react with the gas containing hydrogen atoms, causing the transition metal-containing particles to aggregate and shrink in volume, which generates tension that pulls the precursor of the joint 30, resulting in the inwardly curved side surface 32; however, the process of forming the joint 30 is not limited thereto.

[0025] As an index expressing the curvature of the side surface 32, the mid-height H of the joint portion 30 is 1 / 2 Sectional length L at 1 / 2 can be used. Sectional length L 1 / 2 is smaller than the contact cross-sectional length L0, the joint 30 has a surface in which the side surface 32 curves toward the center, and the cross-sectional length L 1 / 2 Since the difference between the intermediate height H and the contact cross-sectional length L0 is large, the joint 30 has a side surface 32 with a larger curvature. 1 / 2 The “height H” used to calculate is the distance from the base material 20 to the highest point of the joint 30, as shown in FIG.

[0026] Section length L 1 / 2is preferably 1.0 to 500 nm, more preferably 5.0 to 400 nm, and further preferably 10 to 300 nm. When the contact cross-sectional length L0 is within the above range, the adhesion between the bonding portion 30 and the substrate 20 is further improved, and thus the adhesion between the particle layer 10 and the substrate 20 tends to be further improved.

[0027] Section length L 1 / 2 and the ratio of the contact cross-sectional length L0 (L 1 / 2 / L0) is preferably 0.1 to 1.0, more preferably 0.2 to 0.9, and further preferably 0.3 to 0.8. 1 / 2 When / L0 is within the above range, the adhesion between the joint 30 and the substrate 20 is improved, and therefore the adhesion between the particle layer 10 and the substrate 20 tends to be improved.

[0028] Furthermore, the contact angle θ between the side surface of the joint 30 and the substrate 20 can also be used as an index expressing the curvature of the side surface 32. The contact angle θ is preferably 90° or less, more preferably 80° or less, and even more preferably 70° or less. When the contact angle θ is within the above range, the adhesion between the particle layer 10 and the substrate 20 tends to be further improved.

[0029] Although the above describes the case where the side surface 32 is curved inward, the side surface 32 may be curved outward. More specifically, in the process of forming the bonding portion 30, if the precursor has a high affinity for the substrate 20 or the particle 12 surface and the contact angle becomes small, the side surface 32 may be curved inward or the cross-sectional length L 1 / 2 On the other hand, in the process of forming the bonding portion 30, if the precursor has a low affinity for the substrate 20 or the surface of the particle 12 and the contact angle becomes large, the side surface 32 may be curved outward or the cross-sectional length L 1 / 2 becomes larger than the contact cross-sectional length L0, or the contact angle exceeds 90°. However, the process for forming the bonded portion 30 is not limited to this.

[0030] In this embodiment, the distance between the tip of the particle 12 and the surface of the substrate 20 is defined as the gap G. The gap G between the protruding particle 12 and the substrate 20 joined by the joint 30 is preferably 1.0 to 100 nm, more preferably 3.0 to 75 nm, and further preferably 5.0 to 50 nm. When the gap G is within the above range, the adhesion between the particle layer 10 and the substrate 20 tends to be further improved.

[0031] 1.1.3.Measurement method As described above, the bond 30 is a bond between the particle 12 and the substrate 20 that can be confirmed in a reflected electron image, and can be confirmed in a transmitted electron image as a portion that has a lower contrast than the particle layer and the substrate. Various parameters related to the contact surfaces 31, 33 and the side surface 32 of the bond 30 can also be measured by the reflected electron image and the transmitted electron image, mainly the transmitted electron image.

[0032] When the particle layer 10 is a thin metal wire described later, the various parameters related to the joints 30 can be calculated for each joint included in one cross section (see Figures 1 to 3) and the average values ​​thereof can be obtained.

[0033] 1.1.4.Adjustment method The bond 30 can be formed between the tip of the particle 12 and the substrate 20 by controlling whether or not an exposure step is performed in the manufacturing method described below, and by controlling the conditions of the exposure step and the plasma reaction step. In addition, various parameters related to the contact surfaces 31, 33 and the side surface 32 of the bond 30 can also be controlled by controlling the particle growth of the particle 12 by controlling whether or not an exposure step is performed, and by controlling the conditions of the exposure step and the plasma reaction step.

[0034] 1.2.Particle layer The particle layer 10 is formed by bonding particles containing a transition metal, and is not particularly limited as long as it has particles 12 protruding from the substrate 20, and may have pores 11. This particle layer 10 provides the electrical conductivity of the conductive sheet 100.

[0035] As shown in FIG. 2, the particle layer 10 may have a relatively large number of pores 11 at the interface between the substrate 20 and the particle layer 10. More specifically, when the precursor thin film is plasma-treated under specific conditions by the manufacturing method described later, the growth of sintered particles of the transition metal preferentially proceeds on the surface side of the precursor thin film, and the increase in pores proceeds on the interface side between the substrate 20 and the particle layer 10. As a result, pores 11 are likely to be formed at the interface between the substrate 20 and the particle layer 10, and the particle layer 10 thus formed is considered to have particles 12 protruding from the interface side between the substrate 20 and the particle layer 10. However, the reason for the formation of the particles 12 is not limited to the above.

[0036] In this manner, the structure having a relatively large number of pores 11 at the interface between the substrate 20 and the particle layer 10 makes the particle layer 10 less susceptible to breakage even when stress such as bending of the substrate 20 is applied. On the other hand, when a relatively large number of pores 11 are present at the interface between the substrate 20 and the particle layer 10, the contact area between the substrate 20 and the particle layer 10 becomes small, so that it is generally considered that the particle layer 10 is easily peeled off from the substrate 20. However, in this embodiment, the presence of the above-mentioned joint 30 makes it possible to ensure adhesion between the particle layer and the substrate.

[0037] The curvature of the portion of the protruding particle 12 that contacts the joint 30 is preferably 1.0 to 1000 μm. -1 More preferably, the thickness is 20 to 100 μm. -1 The curvature of the protruding particles 12 is within the above range, so that the adhesion to the joint 30 tends to be improved. In addition, the curvature of the particles 12 is within the above range, so that the growth of the sintered particles by the plasma treatment can be recognized as being sufficiently grown even on the interface side between the substrate 20 and the particle layer 10, and the particle layer 10 having such particles 12 tends to have excellent electrical conductivity and low sheet resistance. The portion in contact with the joint 30 can also be rephrased as the portion of the particles 12 corresponding to the contact surface 33.

[0038] The average particle size of the particles constituting the particulate layer 10 is preferably 1.0 to 500 nm, more preferably 5.0 to 400 nm, and even more preferably 10 to 300 nm. When the average particle size is within the above range, the sheet resistance tends to be further reduced. The average particle size of the particles constituting the particulate layer 10 can be measured by a transmission electron image of the cross section of the particulate layer 10.

[0039] 1.2.1. Composition The particle layer 10 of the present embodiment contains a transition metal, and may contain other atoms such as oxygen atoms, carbon atoms, phosphorus atoms, etc., as necessary. The transition metal may exist in the form of a metal element or in the form of a metal compound such as an oxide.

[0040] In the particle layer 10, the transition metal may exist in the form of a metal element or a metal compound such as an oxide. The transition metal atoms contained in the particle layer 10 are not particularly limited as long as they are metals of Groups 3 to 11 in the IUPAC periodic table, but preferably contain a metal of Group 11, more preferably contain silver or copper, and even more preferably contain copper. By using such a transition metal, the conductivity of the particle layer 10 tends to be further improved.

[0041] The type of metal compound containing a transition metal is not particularly limited, but examples thereof include sulfides, selenides, tellurides, nitrides, phosphides, oxides, etc. Among these, oxides are preferable because they are less harmful to the human body and relatively easy to produce.

[0042] 1.2.2.Film Thickness The thickness of the particulate layer 10 is preferably 30 nm to 1000 μm, more preferably 50 nm to 100 μm, even more preferably 100 nm to 10 μm, still more preferably 200 to 1000 nm, and even more preferably 300 to 500 nm. When the thickness is 30 nm or more, the sheet resistance of the particulate layer 10 tends to be lower. When the thickness is 1000 μm or less, the adhesion of the particulate layer 10 to the substrate tends to be improved. When the thickness is 1000 μm or less, the pattern of the particulate layer 10 tends to be formed more easily.

[0043] The film thickness of the particle layer 10 can be determined by a cross-sectional STEM-EDX evaluation of the particle layer 10 described later. More specifically, a region in which the atomic concentration of the transition metal in the conductive thin film is 20% or more is defined as the film thickness of the conductive thin film, and the average value of the film thicknesses measured at any three positions can be taken as the film thickness of the particle layer 10. Note that the particle layer 10 of this embodiment may be a thin film having a uniform thickness, or may be a thin film having unevenness on the surface or having thin portions depending on the position of the particle layer 10.

[0044] Regardless of whether or not there are a relatively large number of pores 11 at the interface between the substrate 20 and the particulate layer 10, the thickness of the particulate layer 10 in this embodiment is defined as the distance from the surface of the substrate 20 to the surface of the particulate layer 10.

[0045] Patterns The particulate layer 10 may have a continuous pattern with openings, or a solid pattern without openings. The pattern of the particulate layer 10 can be designed according to the intended use of the electronic device, and may be a regular pattern or an irregular pattern. Here, the opening refers to a portion where no conductive sheet is present, and light can pass through the opening portion. In addition, the continuous pattern refers to a pattern that is confirmed to be connected (contacted) with an optical microscope, and such a pattern is electrically connected.

[0046] Among these, the particle layer 10 preferably has a continuous pattern having openings. By providing openings in this way, a light-transmitting conductive sheet can be obtained. The continuous pattern having openings is not particularly limited, but is preferably, for example, a pattern formed by a plurality of crossing thin lines. In this case, the thin lines correspond to the conductive sheet, and the gaps between the thin lines are the openings.

[0047] Specific examples of the pattern formed by a plurality of thin wires are described below, but the pattern in this embodiment is not limited to the following. In the following, the thin metal wires refer to the particle layer 10 having a thin line shape in a plan view, and the thin metal wire pattern refers to a pattern formed by a plurality of thin metal wires.

[0048] FIG. 4 is a schematic top view showing an example of a pattern 40 of the conductive sheet 100 of this embodiment. FIG. 4 is a top view of the conductive sheet 100 in which the particle layer 10 is disposed on the substrate 20, as viewed from the side on which the particle layer 10 is formed. In FIG. 4, the particle layer 10 is in the form of thin lines, and is shown as a state in which the thin lines cross in a grid shape. Here, the thin line-shaped particle layer 10 is called a thin metal wire 10'. The cross section of FIG. 1 above shows the cross section of this thin metal wire 10' taken along the line A-A'.

[0049] As shown in Fig. 4, the continuous pattern refers to, for example, a configuration in which a plurality of thin metal wires 10' cross each other to form a continuous layer, thereby allowing electrical current to flow between any two points on the particle layer 10 spreading in the planar direction. Furthermore, having an opening refers to, for example, having discontinuous openings 50 between a plurality of thin metal wires 10'. In this embodiment, the conductive continuous layer and openings formed by the thin metal wires 10' are referred to as a thin metal wire pattern 40.

[0050] Here, the line width W of the fine metal wires 10' constituting the fine metal wire pattern 40 refers to the line width of the fine metal wires 10' when the fine metal wires 10' are projected onto the surface of the substrate 20 from the side of the substrate 20 on which the fine metal wire pattern 40 is disposed. The "projected line width" is defined as the width of the interface between the particle layer 10 and the substrate, for example, as shown in Fig. 1, when the interface is the widest. The pitch P is defined as the sum of the line width W and the distance L between the fine metal wires.

[0051] Specific examples of the above-mentioned fine metal wire pattern include a mesh pattern formed by a plurality of fine metal wires crossing each other in a mesh pattern, and a line pattern formed with a plurality of approximately parallel fine metal wires. The fine metal wire pattern may also be a combination of a mesh pattern and a line pattern. The mesh of the mesh pattern may be a square or rectangle, or a polygon such as a rhombus. The fine metal wires constituting the line pattern may be straight or curved. Furthermore, the fine metal wires constituting the mesh pattern may also be curved.

[0052] Line width The line width W is preferably from 100 nm to 1000 μm, more preferably from 200 nm to 500 μm, even more preferably from 300 nm to 100 μm, still more preferably from 400 nm to 50 μm, and even more preferably from 500 nm to 5.0 μm.

[0053] By making the line width W of the thin metal wire 100 nm or more, the conductivity of the thin metal wire can be sufficiently ensured, and the sheet resistance tends to be further reduced. In addition, the decrease in conductivity due to oxidation or corrosion of the surface of the thin metal wire can be sufficiently suppressed. Furthermore, for the same aperture ratio, the thinner the line width of the thin metal wire, the more the number of thin metal wires can be increased. This makes the electric field distribution of the conductive sheet more uniform, making it possible to fabricate electronic devices with higher resolution. In addition, even if some of the thin metal wires are broken, the other thin metal wires can compensate for the resulting effect.

[0054] On the other hand, by having the line width W of the thin metal wires be 5.0 μm or less, the visibility of the thin metal wires is further reduced, and the transparency of the conductive sheet and the conductive sheet including the same tends to be further improved.

[0055] Aspect Ratio The aspect ratio, which is expressed by the thickness T of the thin metal wire relative to the line width W of the thin metal wire, is preferably 0.05 to 1.00, more preferably 0.08 to 0.90, and further preferably 0.10 to 0.80. When the line width W is constant, the larger the aspect ratio, the more the conductivity tends to improve without decreasing the transmittance. In addition, by keeping the aspect ratio at 1.00 or less, a decrease in transmittance due to an excessively thick film thickness tends to be suppressed.

[0056] Pitch The pitch P is preferably 1.0 to 1000 μm, more preferably 5.0 to 500 μm, even more preferably 50 to 250 μm, and even more preferably 100 to 250 μm. When the pitch P is 1.0 μm or more, the transparency of the conductive sheet and the conductive sheet including the same tends to be improved. When the pitch P is 1000 μm or less, the conductivity tends to be improved. When the shape of the thin metal line pattern is a mesh pattern, the pitch of the thin metal line pattern with a line width of 1 μm is set to 200 μm, so that the aperture ratio can be 99%.

[0057] 1.2.7.Aperture ratio The aperture ratio of the thin metal line pattern is preferably 60% or more, more preferably 70% or more, even more preferably 80% or more, and particularly preferably 90% or more. When the aperture ratio of the thin metal line pattern is 60% or more, the transmittance of the conductive sheet tends to be further improved.

[0058] The aperture ratio of the thin metal line pattern is preferably less than 100%, more preferably 95% or less, even more preferably 90% or less, still more preferably 80% or less, even more preferably 70% or less, and particularly preferably 60% or less. The aperture ratio of the thin metal line pattern being less than 100% tends to further improve the conductivity of the conductive sheet.

[0059] The appropriate aperture ratio of the thin metal line pattern varies depending on the shape of the thin metal line pattern. In addition, the aperture ratio of the thin metal line pattern can be appropriately combined with the above upper and lower limits depending on the required performance (transmittance and sheet resistance) of the target electronic device.

[0060] The "aperture ratio of the thin metal line pattern" can be calculated for the region on the substrate where the thin metal line pattern is formed by the following formula. The region on the substrate where the thin metal line pattern is formed excludes edges and the like where the thin metal line pattern is not formed. Aperture ratio of thin metal line pattern = (1 - area occupied by thin metal line pattern / area of ​​transparent substrate) x 100

[0061] The line width W, aspect ratio, and pitch P of the thin metal line pattern can be confirmed by observing the cross section of the conductive sheet with an electron microscope or the like. The line width and pitch of the thin metal line pattern can also be observed with a laser microscope or optical microscope. Since the pitch P and the aperture ratio have a relational expression described below, if one is known, the other can be calculated. Methods for adjusting the line width W, aspect ratio, and pitch P of the thin metal line pattern to the desired range include a method of adjusting the grooves of a plate used in the manufacturing method of a conductive sheet described below, and a method of adjusting the average particle size of metal particles in an ink.

[0062] 1.2.8.Visible light transmittance The visible light transmittance of the conductive sheet is preferably 70 to 99%, more preferably 75 to 95%, and further preferably 80 to 90%. The visible light transmittance can be measured by calculating the average transmittance in the visible light range (360 to 830 nm) in accordance with the total light transmittance of JIS K 7361-1:1997. The visible light transmittance of the patterned thin film tends to be improved by reducing the line width of the thin metal line pattern or improving the aperture ratio.

[0063] Sheet Resistance The sheet resistance of the conductive sheet is preferably 0.001 to 20 Ωcm -2 More preferably, it is 0.01 to 17.5 Ωcm -2 and more preferably 0.01 to 15 Ωcm -2 and preferably 0.1 to 10 Ωcm -2 The lower the sheet resistance, the more the electrical conductivity tends to improve.

[0064] The sheet resistance of a conductive sheet tends to decrease by improving the aspect ratio (height) of the thin metal wires. It can also be adjusted by selecting the type of metal material that makes up the thin metal wires.

[0065] 1.2.10. Haze The haze of the conductive sheet is preferably 0.01 to 5.00%, more preferably 0.01 to 3.00%, and even more preferably 0.01 to 1.00%. When the haze is 5.00% or less, the clouding of the conductive sheet with respect to visible light tends to be further suppressed. The haze in this specification can be measured in accordance with the haze of JIS K 7136:2000.

[0066] 1.3. Base material The substrate can be appropriately selected according to the application of the conductive sheet, and is not particularly limited. For example, transparent inorganic substrates such as glass, opaque inorganic substrates such as metal plates, transparent or opaque organic substrates such as plastic films can be mentioned. Among these, plastic is preferable from the viewpoint of obtaining a flexible and transparent conductive sheet. In addition, these substrates may have an arbitrary layer on the surface, or may be subjected to an arbitrary surface treatment such as corona treatment.

[0067] The substrate may be in the form of a plate or a film, with the film being preferred from the viewpoint of excellent freedom in shape.

[0068] The plastic is not particularly limited, but examples thereof include transparent organic substrates such as acrylic acid esters, methacrylic acid esters, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyarylate, polyvinyl chloride, polyethylene, polypropylene, polystyrene, nylon, aromatic polyamide, polyether ether ketone, polysulfone, polyethersulfone, polyimide, and polyetherimide.

[0069] Among these, it is preferable to use polyethylene terephthalate (PET) from the viewpoint of high productivity including the cost reduction effect for manufacturing the conductive sheet. Also, it is preferable to use polyimide from the viewpoint of excellent heat resistance of the conductive sheet. Furthermore, it is preferable to use polyethylene terephthalate and / or polyethylene naphthalate from the viewpoint of advantageous adhesion between the thin film and the substrate.

[0070] The substrate of the thin film used in this embodiment may be made of one material or may be a laminate of two or more materials. In addition, when the transparent substrate is a multilayer body in which two or more materials are laminated, the transparent substrate may be a laminate of organic substrates or inorganic substrates, or a laminate of an organic substrate and an inorganic substrate.

[0071] From the viewpoint of excellent degree of freedom in shape and / or excellent transparency, the thickness of the substrate is preferably 5.0 to 500 μm, more preferably 5.0 to 300 μm, and further preferably 10 to 100 μm.

[0072] 1.3.1.Surface layer The substrate may have multiple layers, and may have a surface layer in the portion in contact with the conductive sheet. By laminating the surface layer on the substrate, it is possible to prevent etching of the substrate in the portion not covered with the thin metal line pattern by plasma or the like when the metal components in the ink are sintered by a baking means such as plasma.

[0073] The components contained in the surface layer are not particularly limited, and examples thereof include silicon compounds (e.g., (poly)silanes, (poly)silazanes, (poly)silthians, (poly)siloxanes, silicon, silicon carbide, silicon oxide, silicon nitride, silicon chloride, silicate salts, zeolites, silicides, etc.), aluminum compounds (e.g., aluminum oxide, etc.), magnesium compounds (e.g., magnesium fluoride), etc. The polysilanes, polysilazanes, polysilthians, and polysiloxanes may have a linear or branched, cyclic, or network-like form. These components may be used alone or in combination of two or more.

[0074] Among these, silicon compounds, aluminum oxide, and magnesium fluoride are preferred, and silicon oxide, silicon nitride, aluminum oxide, and magnesium fluoride are more preferred.By using such components, durability against plasma is improved, and the adhesion between the conductive sheet and the substrate is improved.In addition, by using such components, the transparency and durability of the conductive sheet are improved, and the productivity that contributes to the cost reduction effect for manufacturing the conductive sheet is improved.

[0075] The surface layer can be formed by a vapor phase film formation method such as physical vapor deposition (PVD) or chemical vapor deposition (CVD), or by a method of applying and drying a composition in which the components contained in the surface layer are dispersed in a dispersion medium. This composition may contain a dispersant, a surfactant, a binder, etc., as necessary.

[0076] In addition, when the surface layer is included, silicon may be incorporated into the conductive sheet through a plasma reaction. The silicon atom Si contained in the metal fine wire may exist in the form of a silicon atom or a silicon compound, or in the form in which the silicon atom or the silicon compound is bonded to a metal atom (e.g., Si-M, Si-OM, etc.).

[0077] Thickness The thickness of the surface layer is preferably 0.01 to 500 μm, more preferably 0.05 to 300 μm, and even more preferably 0.10 to 200 μm. When the thickness of the surface layer is 0.01 μm or more, the adhesion between the conductive sheet and the substrate tends to be further improved. Also, when the thickness of the surface layer is 500 μm or less, the flexibility of the substrate can be ensured.

[0078] Volume resistivity The surface layer preferably has an antistatic function to prevent breakage of the thin metal wire pattern due to static electricity. From the viewpoint of having the antistatic function, the surface layer preferably contains at least one of a conductive inorganic oxide and a conductive organic compound.

[0079] From the viewpoint of antistatic function, the volume resistivity of the surface layer is preferably 100 to 100,000 Ωcm, preferably 1,000 to 10,000 Ωcm, and preferably 2,000 to 8,000 Ωcm. When the volume resistivity of the surface layer is 100,000 Ωcm or less, the antistatic function tends to be further improved. In addition, when the volume resistivity of the surface layer is 100 Ωcm or more, the electrical conductivity between the metal thin line patterns is further reduced, and the surface layer can be suitably used for applications such as touch panels.

[0080] The volume resistivity can be adjusted by the content of conductive inorganic oxides and conductive organic compounds in the surface layer. For example, if the surface layer contains silicon oxide (volume resistivity 1014 Ω·cm or more), which has high plasma resistance, and an organosilane compound, which is a conductive organic compound, the volume resistivity can be reduced by increasing the content of the organosilane compound. On the other hand, although the volume resistivity increases by increasing the content of silicon oxide, it can be made into a thin film because of its high plasma resistance, and the optical properties are not impaired.

[0081] 1.4.Protective layer The conductive sheet of the present embodiment may have a protective layer (not shown) on the particulate layer 10. The protective layer can be formed so as to sandwich the particulate layer 10 together with the substrate 20.

[0082] The protective layer is not particularly limited as long as it has transparency and can exhibit good adhesion to the conductive sheet or substrate. For example, thermosetting resins such as phenolic resin, thermosetting epoxy resin, thermosetting polyimide, melamine resin, urea resin, unsaturated polyester resin, alkyd resin, polyurethane, diallyl phthalate resin, and silicone resin; UV-curable resins such as urethane acrylate, acrylic resin acrylate, epoxy acrylate, silicone acrylate, and UV-curable epoxy resin; and commercially available coating agents can be used.

[0083] 2. Manufacturing method of conductive sheet The method for producing a conductive sheet of the present embodiment includes a film formation step of forming a precursor thin film on a substrate, an exposure step of exposing the precursor thin film to a gas containing hydrogen atoms at a partial pressure of 50 to 1000 Pa for 50 to 1000 seconds, and a plasma reaction step of reacting the precursor thin film with plasma for 120 to 2000 seconds to obtain a conductive sheet, and may optionally include a surface layer formation step of forming a surface layer on the substrate before the film formation step.

[0084] 2.1. Surface layer formation process The surface layer forming step is a step of forming the above-mentioned surface layer on the substrate. For example, when a plastic substrate is used, the surface layer can prevent the plastic from being denatured or etched by the plasma reaction.

[0085] A specific example of the surface layer forming method is a method of forming a surface layer by forming a film of a component that forms a surface layer on the surface of a transparent substrate using a gas phase film forming method such as physical vapor deposition (PVD) or chemical vapor deposition (CVD). Another specific example of the surface layer forming step is a method of forming a surface layer by applying a composition in which the component that forms the surface layer is dispersed in a dispersion medium to the surface of a transparent substrate and drying the composition. In addition, the surface layer forming composition may contain a dispersant, a surfactant, etc., as necessary.

[0086] In the surface layer forming step, it is preferable to use the above-mentioned silicon compound as a component for forming the surface layer.

[0087] 2.2. Film formation process The film forming step is a step of forming a precursor thin film on a substrate.

[0088] 2.2.1. Precursor thin film The precursor thin film contains a transition metal, and is turned into the conductive sheet of this embodiment by subjecting it to a plasma reaction process described later. As already described, the conductive sheet obtained by subjecting the precursor thin film to plasma treatment in this manner is a conductive sheet with excellent adhesion even when a fine pattern is formed.

[0089] Such a precursor thin film can be formed by various methods such as a dry method using a vacuum device, etc., a wet method using an ink, etc. Among these, a method of forming a precursor thin film by printing an ink on a substrate is preferred from the viewpoint of suitability for large-scale production.

[0090] The printing method that can be used is not particularly limited, and examples thereof include letterpress printing, gravure printing, bar coating, spray coating, spin coating, reverse transfer printing, etc. Among these, from the viewpoint of being able to print a relatively precise pattern, formation of the precursor thin film by a plate printing method is preferred.

[0091] Examples of plate-based printing methods include a step of coating the surface of a transfer medium with ink, a step of contacting the ink-coated transfer medium surface with the convex surface of a letterpress plate to transfer a portion of the ink on the transfer medium surface to the convex surface of the letterpress plate, and a step of contacting the transfer medium surface after some of the ink has been transferred with the surface of a substrate to transfer the ink remaining on the transfer medium surface to the surface of the substrate.

[0092] For example, in such a printing method, various shapes of the precursor thin film, such as thickness, width, pitch, etc., and the concentration of each atom contained in the precursor thin film can be controlled by adjusting the printing conditions and ink.

[0093] Ink The ink used in the above printing method contains a metal component and a solvent, and may contain a surfactant, a dispersant, a reducing agent, etc., as necessary.

[0094] 2.2.2.1. Metal particles The metal component may be contained in the ink as metal particles or as a metal complex. Among these, it is preferable that the metal component is contained in the ink as metal particles. As the metal particles, as long as they contain the above-mentioned transition metal atoms, they may be metal oxides such as copper oxide or other metal compounds, or core / shell particles in which the core part is copper and the shell part is copper oxide. Among these, metal oxides such as copper oxide are preferable from the viewpoint of handling.

[0095] The average primary particle size of the metal particles is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 30 nm or less. The lower limit of the average primary particle size of the metal particles is not particularly limited, but may be 1 nm or more. From the viewpoint of making the line width W of the obtained thin metal wires thinner, the average primary particle size of the metal particles is preferably 100 nm or less.

[0096] The average secondary particle size of the metal particles is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 30 nm or less. From the viewpoint of excellent coatability during thin film formation, it is preferable that each particle is monodispersed and the average secondary particle size is close to the average primary particle size.

[0097] In this embodiment, the "average primary particle size" refers to the particle size of each individual metal particle (so-called primary particle), and is distinguished from the average secondary particle size, which is the particle size of an aggregate (so-called secondary particle) formed by multiple metal particles gathering together.

[0098] Surfactants The surfactant is not particularly limited, but examples thereof include fluorine-based surfactants and silicone-based surfactants. By using such surfactants, the coatability of the ink on the transfer medium (blanket) and the smoothness of the coated ink are improved, and a more uniform coating film tends to be obtained. It is preferable that the surfactant is configured to be capable of dispersing metal components and to be unlikely to remain after baking.

[0099] Solvent The ink solvent is preferably an organic solvent from the viewpoints of excellent storage stability and small light loss. From the above viewpoints, the organic solvent is preferably an alcohol. From the above viewpoints, the number of carbon atoms in the organic solvent is preferably 1 to 7, more preferably 2 or more, more preferably 5 or less, or 4 or less, and most preferably 2.Examples of the solvent include water, propylene glycol monomethyl ether acetate, 3-methoxy-3-methyl-butyl acetate, ethoxyethyl propionate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol tertiary butyl ether, dipropylene glycol monomethyl ether, ethylene glycol butyl ether, ethylene glycol ethyl ether, ethylene glycol methyl ether, ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2-pentanediol, 2-methylpentane-2,4-diol, 2,5-hexanediol, 2,4-heptanediol, 2-ethylhexane-1,3-diol, diethylene glycol, hexanediol, octanediol, triethylene glycol, tri-1,2-propylene glycol, glycerol, ethylene glycol monohexyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl acetate, diethylene glycol, monoethyl ether acetate, methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, 2-butanol, t-butanol, n-pentanol, i-pentanol, 2-methylbutanol, 2-pentanol, t-pentanol, 3-methoxybutanol, n-hexanol, 2-methylpentanol, 1-hexanol, 2-hexanol, 2-ethylbutanol, 1-heptanol, 2-heptanol, 3-heptanol, n-octanol, 2-ethylhexanol, 2-octanol, n-nonyl Examples of the alcohol include alcohol, 2,6-dimethyl-4-heptanol, n-decanol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, benzyl alcohol, and diacetone alcohol. From the viewpoints of excellent storage stability and low light loss, methanol, ethanol, propanol, butanol, pentanol, hexanol, heptanol, and isomers thereof are more preferable, ethanol, propanol, butanol, and isomers thereof are even more preferable, and ethanol is the most preferable.

[0100] Dispersants The dispersant is not particularly limited, but examples thereof include dispersants that non-covalently bond or interact with metal components, and dispersants that covalently bond with metal components. Examples of functional groups that non-covalently bond or interact with metal components include dispersants having a phosphate group. By using such dispersants, the dispersibility of metal components tends to be further improved.

[0101] 2.3. Exposure process The exposure step is a step of exposing the precursor thin film to a gas containing hydrogen atoms at a partial pressure of 50 to 1000 Pa for 50 to 1000 seconds. By including such an exposure step, a predetermined amount of molecules of the gas containing hydrogen atoms are taken in and / or adsorbed to the precursor thin film. It is considered that a bond is formed by carrying out a plasma reaction step described later thereafter. However, the mechanism of forming the bond is not limited to the above.

[0102] The gas containing hydrogen atoms is not particularly limited, but examples thereof include hydrogen, water, ammonia, and methane. Among these, from the viewpoint of excellent formation of the bonded portion 30, hydrogen or water is preferable, and hydrogen is more preferable. The gas containing hydrogen atoms may be one or more types of molecules. In addition, the atmosphere of the exposure step is not particularly limited as long as a gas containing hydrogen atoms is used at a predetermined partial pressure, and other gases may be mixed. The other gas is not particularly limited, but examples thereof include rare gases such as helium. In addition, it is preferable that the amount of oxidizing gas such as oxygen mixed is small. In particular, the partial pressure of the oxidizing gas such as oxygen is preferably less than the partial pressure of the gas containing hydrogen atoms, more preferably less than half, and even more preferably less than 1 / 10. It is more preferable.

[0103] The partial pressure of the gas in the exposure step is 50 to 1000 Pa, preferably 50 to 750 Pa, and more preferably 50 to 500 Pa. When the partial pressure is within the above range, adsorption of the gas into the precursor thin film proceeds favorably, and a bond tends to be formed more easily.

[0104] The exposure time to the gas is 50 to 1000 seconds, preferably 100 to 750 seconds, and more preferably 150 to 500 seconds. When the exposure time is within the above range, adsorption of the gas into the precursor thin film proceeds favorably, and a bond tends to be formed more easily.

[0105] The temperature in the exposure step is preferably 0 to 300° C., preferably 10 to 200° C., and more preferably 15 to 250° C. When the exposure temperature is within the above range, adsorption of the gas into the precursor thin film proceeds favorably, and a bond tends to be formed more easily.

[0106] 2.4.Plasma reaction process The plasma reaction process is a process in which the precursor thin film after the exposure process is reacted with plasma for 120 to 2000 seconds to obtain a conductive sheet. This causes the precursor thin film to be baked, and the metal particles in the ink are sintered to form a particle layer (conductive thin film), and a joint that joins the particle layer to the substrate is formed. This makes it possible to obtain a conductive sheet that is excellent in conductivity and adhesion to the substrate. In addition, by making the atmosphere during the plasma reaction a gas containing hydrogen atoms, the oxygen concentration in the conductive sheet can also be adjusted.

[0107] Plasma can be generated by various methods. Among them, microwave plasma and high frequency plasma are preferable because they are relatively easy to control, and microwave plasma is more preferable from the viewpoint of reducing contamination caused by electrodes for generating plasma in the apparatus.

[0108] The microwave output of the microwave plasma is preferably 0.5 to 10 kW, more preferably 0.5 to 5.0 kW. By using a microwave output of 0.5 kW or more, the adhesion between the obtained conductive sheet and the substrate is improved, and the plasma reaction time can be shortened. In addition, by using a microwave output of 10 kW or less, etching or modification of the substrate by the plasma tends to be suppressed.

[0109] The treatment time of the plasma reaction is 120 to 2000 seconds, preferably 120 to 1000 seconds, and more preferably 150 to 500 seconds. By setting the treatment time to 120 seconds or more, a particle layer is formed and a bonding portion is formed, thereby further improving the adhesion between the conductive sheet and the substrate. In addition, by setting the treatment time to 2000 seconds or less, the productivity of the conductive sheet tends to be further improved.

[0110] The atmosphere of the plasma reaction preferably contains a gas containing molecules containing hydrogen atoms or a rare gas. The gas containing molecules containing hydrogen atoms is not particularly limited, but for example, a gas containing hydrogen molecules or water molecules is preferable, and a gas containing hydrogen molecules is more preferable. By using such a gas containing molecules containing hydrogen atoms, the conductivity of the conductive sheet to be manufactured tends to be further improved. The partial pressure of the gas containing molecules containing hydrogen atoms is preferably 0.1 to 1000 Pa, more preferably 1.0 to 500 Pa, and even more preferably 10 to 300 Pa. The gas containing molecules containing hydrogen atoms may be one or more types of molecules.

[0111] The rare gas is not particularly limited, but examples thereof include helium, argon, xenon, and krypton. Among these, helium or argon, which have relatively small molecular weights, are preferred, and helium is most preferred, from the viewpoint of reducing sample etching by these plasmas. By using such a rare gas, the plasma reaction can be more easily controlled.

[0112] The gas containing hydrogen atoms and the rare gas may be mixed and used, or other gases may be mixed therewith. From the viewpoint of having reducing properties and being able to relatively easily control the reduction reaction, it is preferable to use both the gas containing hydrogen atoms and the rare gas. Specifically, it is preferable to use a gas containing hydrogen molecules and / or water molecules and helium.

[0113] The pressure of the plasma reaction may be under pressure, reduced pressure, or atmospheric pressure. Among these, reduced pressure is preferable from the viewpoint of lengthening the mean free path of the plasma. Specifically, the pressure is preferably 0.1 to 1000 Pa, more preferably 1.0 to 500 Pa, and further preferably 10 to 300 Pa. When the pressure is 0.1 Pa or more, the mean free path of the plasma tends to be longer. Furthermore, when the pressure is 1000 Pa, it is possible to use a larger amount of gas or rare gas, which is a molecule containing hydrogen atoms.

[0114] 3. Touch Panel The touch panel of the present embodiment is not particularly limited as long as it includes the conductive sheet. For example, in a capacitive touch panel, two conductive sheets are present on the front and back sides of an insulator, and the two conductive sheets face each other so that, for example, the line patterns of thin metal wires cross. The conductive sheets are connected to an extraction electrode, and the extraction electrode connects the thin metal wires to a controller (such as a CPU) for switching the current supply to the thin metal wires.

[0115] The touch panel of the present embodiment is not limited to a capacitive type, and may be a resistive film type, a projected capacitive type, a surface capacitive type, or the like.

[0116] 4. Display The display of the present embodiment is not particularly limited as long as it includes the conductive sheet. For example, an organic electroluminescence (EL) display has a structure in which an organic EL film is sandwiched between electrodes, and the conductive sheet can be used as one of the electrodes. Also, a liquid crystal display has a structure in which a liquid crystal layer is sandwiched between electrodes, and the conductive sheet can be used as one of the electrodes.

[0117] 5. Heater The heater of the present embodiment is not particularly limited as long as it includes the conductive sheet. For example, an electric heater has an electric heating part that generates Joule heat when electricity is supplied thereto, and a power supply device that supplies power to the electric heating part, and a conductive sheet can be used as the electric heating part. If the conductive sheet is made transparent, it becomes a transparent heater, and if the conductive sheet is designed to have a high resistance, it becomes a heater with a high heat generation amount.

[0118] For example, the use of the transparent heater is not particularly limited, but examples thereof include anti-fogging or anti-freezing heaters for LED lighting fixtures used in automobile headlamps, taillamps, etc., and anti-fogging or anti-freezing heaters for outdoor LED lighting fixtures used in street lamps, etc.

[0119] 6.Electromagnetic Shielding The electromagnetic wave shield of the present embodiment is not particularly limited as long as it includes the conductive sheet. For example, the electromagnetic wave shield includes a shielding material that reflects or absorbs incident electromagnetic waves, and the conductive sheet can be used as the shielding material.

[0120] 7. Antenna The antenna of the present embodiment is not particularly limited as long as it is equipped with the conductive sheet. For example, an RF tag has a semiconductor element and an antenna connected thereto, which enables transmission and reception of a specific frequency, and the conductive sheet can be used as the antenna. If the conductive sheet is made transparent, it becomes a transparent antenna. EXAMPLES

[0121] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0122] (Evaluation of particle layer and joint morphology) The thickness of the particle layer, the fact that the particle layer was formed by sintering metal particles together, and the presence and shape of joints were determined from the cross-sectional STEM images described below. Furthermore, the pattern shape, line width, and pitch of the particle layer were evaluated using a laser microscope (OLYMPUS, OLS-4500).

[0123] (Cross-sectional STEM image) The obtained conductive sheet was cut with a razor, embedded in a vapor-deposited carbon layer, and sliced ​​to a thickness of about 100 nm with a focused ion beam. The obtained slice was used as a measurement sample and irradiated with an electron beam under the following conditions to prepare an evaluation sample, and a reflected electron image and a transmitted electron image were obtained. [Equipment conditions] STEM: Hitachi High-Technologies Corporation, scanning transmission electron microscope HD-2300A Accelerating voltage: 200kV Measurement magnification: 300,000x or 600,000x

[0124] (Thickness of thin metal wire) Furthermore, the thickness of the metal thin wire was evaluated by STEM-EDX analysis using the above sample. [Equipment conditions] STEM: Hitachi High-Technologies Corporation, scanning transmission electron microscope HD-2300A EDX: EDAX Energy Dispersive X-ray Analysis System Octane T Plus (Software: GENESIS) Accelerating voltage: 200kV Measurement magnification: 100,000x Mapping elements: Cu, O, P, Si, C

[0125] (Sheet resistance evaluation) The sheet resistance was measured using a non-contact resistance meter (NC-700) using eddy current manufactured by NAPSON.

[0126] (Visible light transmittance) The visible light transmittance was calculated by the following method. (Visible light transmittance) = (opening ratio of thin line pattern) × (visible light transmittance of substrate)

[0127] (Adhesion) The adhesion of the particle layer to the substrate was evaluated by the following tape peeling test. The adhesive surface of an adhesive tape (3M No. 610) was brought into contact with the particle layer, and the tape was fixed by rolling a 2N (Newton) roller twice back and forth from above the tape. The fixed tape was peeled off at a speed of 100 mm / min using a 90° peeling tester (Shimadzu Corporation, EZ-S) to perform a tape peeling test. The substrate surface after this tape peeling was observed with a laser microscope (OLYMPUS Corporation, OLS-4500) and compared with the metal thin line before the tape peeling test to determine the peeled area ratio of the metal thin line by the tape peeling test. The smaller this peeled area ratio, the better the adhesion of the thin film to the substrate.

[0128] <Example 1> (Preparation of Transparent Substrate) A surface layer-forming composition containing silicon oxide nanoparticles and a conductive organosilane compound was applied onto a transparent substrate made of polyethylene terephthalate (PET), and then dried to form a surface layer containing silicon oxide with an antistatic function, a thickness of 150 nm, and a volume resistivity of 5000 Ωcm, to obtain a substrate. This substrate has a surface layer laminated on the substrate, PET.

[0129] (Ink Preparation) 20 parts by mass of cuprous oxide nanoparticles with a primary particle size of 21 nm, 4 parts by mass of a dispersant (manufactured by Big Chemie, product name: Disperbyk-145), 1 part by mass of a surfactant (manufactured by Seimi Chemical, product name: S-611), and 75 parts by mass of ethanol were mixed to prepare an ink containing 20% ​​by mass of cuprous oxide nanoparticles.

[0130] (film formation process) First, ink was applied to the surface of the transfer medium, and then the ink-coated surface of the transfer medium was brought into contact with a plate having grooves of a thin metal line pattern, and a portion of the ink on the surface of the transfer medium was transferred to the convex surface of the plate. After that, the surface of the transfer medium coated with the remaining ink was brought into contact with a substrate, and the ink in the form of a thin metal line pattern was transferred onto the substrate. This process produced a precursor thin film. The thickness of this precursor thin film was 680 nm, the line width was 3 μm, and the pitch was 60 μm. Table 1 shows these results.

[0131] (Exposure process) The precursor thin film formed as described above was exposed to a gas containing hydrogen atoms. Specifically, the precursor thin film was exposed to an atmosphere of a mixed gas of hydrogen and helium adjusted so that the hydrogen partial pressure was 100 Pa for 180 seconds.

[0132] (Plasma reaction process) The precursor thin film that had been exposed to the plasma reaction was subjected to a plasma reaction. Specifically, plasma was generated by microwaves generated at an output of 1.5 kW in an atmosphere containing 3% hydrogen by volume and 97% helium by volume under reduced pressure, and the plasma was reacted with the precursor thin film for 300 seconds.

[0133] The thin film of Example 1 was subjected to various evaluations. The results are shown in Table 1. In addition, for four of the joints observed in Example 1, the contact cross-sectional length L0, the cross-sectional length at the mid-height L 1 / 2 The contact angle, curvature, and gap G are summarized in Table 2.

[0134] <Example 2> The same operation as in Example 1 was performed, except that the thickness of the precursor thin film was 360 nm and the reaction time of the plasma reaction step was 180 seconds. The results are shown in Table 1. In addition, for two of the joints observed in Example 2, the contact cross-sectional length L0 and the cross-sectional length at the mid-height L 1 / 2 The contact angle, curvature, and gap G are summarized in Table 2.

[0135] <Example 3> The same operations as in Example 1 were carried out, except that the thickness of the precursor thin film was 360 nm, the gas in the exposure step was changed from hydrogen to water molecules, the output of the plasma reaction step was 0.9 kW, and the reaction time was 120 seconds. The results are shown in Table 1. In addition, for two of the joints observed in Example 3, the contact cross-sectional length L0 and the cross-sectional length at the mid-height L 1 / 2 The contact angle, curvature, and gap G are summarized in Table 2.

[0136] <Comparative Example 1> Except for not carrying out the exposure step and setting the reaction time of the plasma reaction step to 60 seconds, the same operation as in Example 1 was carried out. The results are shown in Table 1.

[0137] [Table 1]

[0138] [Table 2]

[0139] 5 and 6 show backscattered electron images and transmitted electron images of the joints in Examples 1 and 2. [Industrial Applicability]

[0140] 10...particle layer, 10'...thin metal wire, 11...hole, 12...particle, 20...substrate, 30...joint, 31, 33...contact surface, 32...side, 40...thin metal wire pattern, 50...opening, 100...conductive sheet

Claims

1. A substrate; a particle layer having transition metal-containing particles bonded thereto, the particle layer being laminated on the substrate; a joint; The joint portion connects a tip of a particle in the particle layer protruding toward the substrate to the substrate. Conductive sheet.

2. The joint is confirmed as a part having a lower contrast than the particle layer and the substrate in a transmission electron image of a cross section of the conductive sheet obtained by a transmission electron microscope. The conductive sheet according to claim 1.

3. The contact cross-sectional length L 0 is 1.0 nm or more and 500 nm or less; The conductive sheet according to claim 1 or 2.

4. The contact angle θ between the bonding portion and the base material is 90° or less. The conductive sheet according to any one of claims 1 to 3.

5. The cross-sectional length L of the joint at the mid-height 1 / 2 is the contact cross-sectional length L between the base material and the joint. 0 Less than The conductive sheet according to any one of claims 1 to 4.

6. The cross-sectional length L of the joint at the mid-height 1 / 2 and the contact cross-sectional length L of the joint 0 The ratio (L 1 / 2 / L 0 ) is 0.1 or more and 1.0 or less, The conductive sheet according to any one of claims 1 to 5.

7. The curvature of the portion of the protruding particle that contacts the joint is 1.0 μm -1 1000 μm or more -1 Below is the The conductive sheet according to any one of claims 1 to 6.

8. The coverage of the substrate at the joint is 1.0% or more and 50% or less. The conductive sheet according to any one of claims 1 to 7.

9. A gap between the protruding particle and the substrate, which is joined by the joint, is 1 nm or more and 100 nm or less. The conductive sheet according to any one of claims 1 to 8.

10. The substrate has a plurality of layers. The conductive sheet according to any one of claims 1 to 9.

11. The substrate has a surface layer containing a silicon compound. The conductive sheet according to any one of claims 1 to 10.

12. The substrate is a plastic. The conductive sheet according to any one of claims 1 to 11.

13. The plastic is polyethylene terephthalate. The conductive sheet according to claim 12.

14. The transition metal comprises a metal of Group 11 of the IUPAC Periodic Table; The conductive sheet according to any one of claims 1 to 13.

15. The transition metal comprises copper. The conductive sheet according to claim 14.

16. The average particle size of the particles constituting the particle layer is 1.0 nm or more and 500 nm or less. The conductive sheet according to any one of claims 1 to 15.

17. The thickness of the particle layer is 30 nm or more and 1000 μm or less. The conductive sheet according to any one of claims 1 to 16.

18. The particle layer forms a continuous pattern having openings. The conductive sheet according to any one of claims 1 to 17.

19. The pattern is a pattern formed by intersecting a plurality of thin lines. The conductive sheet according to claim 18.

20. The line width of the thin line is 100 nm or more and 1000 μm or less. The conductive sheet according to claim 19.

21. The pitch of the thin lines is 1.0 μm or more and 1000 μm or less. The conductive sheet according to claim 19 or 20.

22. The visible light transmittance is 70% or more and 99% or less. The conductive sheet according to any one of claims 1 to 21.

23. Sheet resistance is 0.001 Ω cm -2 20Ωcm or more -2 Below is the The conductive sheet according to any one of claims 1 to 22.

24. The conductive sheet according to any one of claims 1 to 23 is provided. Touch panel.

25. The conductive sheet according to any one of claims 1 to 23 is provided. display.

26. The conductive sheet according to any one of claims 1 to 23 is provided. Heater.

27. The conductive sheet according to any one of claims 1 to 23 is provided. Electromagnetic wave shielding.

28. The conductive sheet according to any one of claims 1 to 23 is provided. antenna.

29. a film forming step of forming a precursor thin film on a substrate; an exposure step of exposing the precursor thin film to a gas containing hydrogen atoms at a partial pressure of 50 to 1000 Pa for 50 to 1000 seconds; and a plasma reaction step of reacting the precursor thin film exposed to the gas with plasma for 120 seconds to 2000 seconds to obtain a conductive sheet. A method for manufacturing a conductive sheet.

30. The atmosphere of the plasma reaction process contains a gas that is a molecule containing a hydrogen atom. A method for producing the conductive sheet according to claim 29.

31. The atmosphere of the plasma reaction step includes a rare gas. A method for producing the conductive sheet according to claim 29 or 30.

32. In the plasma reaction step, microwave plasma is used. A method for producing a conductive sheet according to any one of claims 29 to 31.

Citation Information

Patent Citations

  • Method for forming conductive film wiring, film structure, electro-optical device, and electronic equipment

    JP2003315813A

  • Laminate and its manufacturing method

    JP2006062135A

  • Conductive substrate

    JP2010192841A

  • Transparent conductive substrate

    JP2012156436A

  • Material for conductive metal thick film formation, and method for forming conductive metal thick film

    JP2013247060A